2022
DOI: 10.1002/ecs2.4154
|View full text |Cite
|
Sign up to set email alerts
|

Removing flowers of a generalist plant changes pollinator visitation, composition, and interaction network structure

Abstract: Pollination is essential for ecosystem functioning, yet our understanding of the empirical consequences of species loss for plant–pollinator interactions remains limited. It is hypothesized that the loss of abundant and generalized (well‐connected) species from a pollination network will have a large effect on the remaining species and their interactions. However, to date, relatively few studies have experimentally removed species from their natural setting to address this hypothesis. We investigated the conse… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 71 publications
1
16
0
Order By: Relevance
“…Nevertheless, similar experiments have induced changes in foraging patterns and/or network structure after temporarily removing a single plant species from relatively small areas (≤0.05 ha) that likely represent a fraction of a pollinator's home range (e.g. Bain et al, 2022; Ferrero et al, 2013; Lopezaraiza–Mikel et al, 2007). For instance, Bain et al (2022) observed that bumblebees ( Bombus spp.)…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Nevertheless, similar experiments have induced changes in foraging patterns and/or network structure after temporarily removing a single plant species from relatively small areas (≤0.05 ha) that likely represent a fraction of a pollinator's home range (e.g. Bain et al, 2022; Ferrero et al, 2013; Lopezaraiza–Mikel et al, 2007). For instance, Bain et al (2022) observed that bumblebees ( Bombus spp.)…”
Section: Discussionmentioning
confidence: 99%
“…Bain et al, 2022; Ferrero et al, 2013; Lopezaraiza–Mikel et al, 2007). For instance, Bain et al (2022) observed that bumblebees ( Bombus spp.) avoided the 15‐m diameter treatment plots where an abundant flower species had been removed—likely contributing to changes in network specialization within those plots—even though these exclusion areas were smaller than the average bumblebee foraging distance (generally 25–100 m in similar habitats: Elliott, 2009; Geib et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, competition between pollinators for floral resources has been shown to affect pollinator behavior both under experimental (Brosi & Briggs, 2013) and field conditions (Magrach et al, 2017). This research has shown that the absence (Brosi & Briggs, 2013) or presence (Magrach et al, 2017) of a highly competitive pollinator species modifies the behavior and visitation patterns of other pollinator species in the community (Bain et al, 2022). However, a larger community‐level analysis of pollinator competitive interactions and how they influence pollinator preference patterns is currently lacking (Bartomeus et al, 2021).…”
Section: Introductionmentioning
confidence: 99%